A Case of Upper Limb Osteomyelitis and Septic Arthritis Presenting as Pseudoparalysis in a Two-Week-Old - Kuldeep Stohr; Guang Xia Xu (Case Reports in Pediatrics)
Pseudoparalysis presenting in infants is a rare manifestation, where infection and trauma are the principle differentials. We present a case of a two-week-old baby boy with pseudoparalysis who was initially diagnosed as Erb’s palsy when presented in the emergency department and later re-presented with signs of sepsis. A later diagnosis of osteomyelitis of the humerus and septic arthritis of the shoulder was made. Despite antibiotic therapy and surgical drainage, the proximal epiphysis of his humerus remains abnormal; however, he has no apparent functional deficit of his right arm at four-year follow-up.